Arabidopsis QWRF1 and QWRF2 Redundantly Modulate Cortical Microtubule Arrangement in Floral Organ Growth and Fertility - Ma, Huifang; Xu, Liyuan; Fu, Ying; Zhu, Lei (Frontiers in Cell and Developmental Biology, 2021)
Floral organ development is fundamental to sexual reproduction in angiosperms. Many key floral regulators (most of which are transcription factors) have been identified and shown to modulate floral meristem determinacy and floral organ identity, but not much is known about the regulation of floral organ growth, which is a critical process by which organs to achieve appropriate morphologies and fulfill their functions. Spatial and temporal control of anisotropic cell expansion following initial cell proliferation is important for organ growth. Cortical microtubules are well known to have important roles in plant cell polar growth/expansion and have been reported to guide the growth and shape of sepals and petals. In this study, we identified two homolog proteins, QWRF1 and QWRF2, which are essential for floral organ growth and plant fertility. We found severely deformed morphologies and symmetries of various floral organs as well as a significant reduction in the seed setting rate in the qwrf1qwrf2 double mutant, although few flower development defects were seen in qwrf1 or qwrf2 single mutants. QWRF1 and QWRF2 display similar expression patterns and are both localized to microtubules in vitro and in vivo. Furthermore, we found altered cortical microtubule organization and arrangements in qwrf1qwrf2 cells, consistent with abnormal cell expansion in different floral organs, which eventually led to poor fertility. Our results suggest that QWRF1 and QWRF2 are likely microtubule-associated proteins with functional redundancy in fertility and floral organ development, which probably exert their effects via regulation of cortical microtubules and anisotropic cell expansion.